HUBUNGAN KEMANDIRIAN ISTRI DENGAN KEHARMONISAN PERKAWINAN PADA TAHAP AWAL PERKAWINAN DI KELURAHAN PAGENTAN KECAMATAN SINGOSARI KABUPATEN MALANG - Maria Agustin; Fabiola Hendrati (Jurnal Psikologi Tabularasa, 2013)
This research is to find out if anything to do with the harmonious marriage of the wife of independence in the early stages of marriage. The population used in this study were those who married at an early stage at the village Pagentan Singosari Malang. Sampling was purposive technique. Methods of data collection using the likert method to scale marital harmony and independence wife. Validity of the results on a scale of marital harmony with significance level 0.05 moving from 0.310 to 0.594 with a valid aitem number by 52, while the results of the validity of the scale independence wife with a significance level of 0.05 moves from 0.304 to 0.551 with aitem valid number by 52. Calculation of variable reliability marital harmony obtained value ? = 0.908 and Reliability wife independence obtained value ? = 0.902. Where two numbers are according to the rules stated reliability is very reliable. The results of data analysis showed no association with the harmonious marriage of the wife of independence in the early stages of marriage with f table f count = 0.525 = 0.176, which f count (0.525) ftable (0.176). The hypothesis states there is a relationship between self and wife with marital harmony in the early stages of marriage (ha) was accepted with a correlation coefficient of 0.525.